1996
DOI: 10.1177/0887302x9601400203
|View full text |Cite
|
Sign up to set email alerts
|

Women 55 Years and Older: Part II. Overall Satisfaction and Dissatisfaction with the Fit of Ready-to-Wear

Abstract: Using the data collected through interview questions, Part II of this nationwide study on women 55 years and older examined factors which might be related to older women's overall satisfaction and dissatisfaction with the fit of ready-to-wear. In general, 70% (n = 4,086) of the respondents indicated dissatisfaction with the fit of ready-towear, while 31% (n = 1,826) indicated satisfaction. By using chi-square analyses, these two groups were then compared on demographics, clothing buying practices, and self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 8 publications
2
61
0
Order By: Relevance
“…Finding clothing that fits well is a challenge for approximately 50% of women (Kurt Salmon Associates 2004, Seckler 2005. Consumers report that pants are one garment that causes the greatest fit dissatisfaction (LaBat and DeLong 1990, Feather et al 1996, Goldsberry et al 1996, Schofield et al 2006, Just-Style.com US 2010. (3) We tested recorded statements of direct concept relationships between body measurement and pattern measurements, specifically, the amount of ease that is added to the body measurement.…”
Section: Rationale For and Limitations Of This Studymentioning
confidence: 98%
“…Finding clothing that fits well is a challenge for approximately 50% of women (Kurt Salmon Associates 2004, Seckler 2005. Consumers report that pants are one garment that causes the greatest fit dissatisfaction (LaBat and DeLong 1990, Feather et al 1996, Goldsberry et al 1996, Schofield et al 2006, Just-Style.com US 2010. (3) We tested recorded statements of direct concept relationships between body measurement and pattern measurements, specifically, the amount of ease that is added to the body measurement.…”
Section: Rationale For and Limitations Of This Studymentioning
confidence: 98%
“…Consumers must guess the actual garment sizes or try them on to identify those that fit them best [33,36]. Research has shown that 52% of women take two or more identical garments of different sizes to the fitting room and that 50% of the customers who order their clothing via a catalog service return garments due to size or fit [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chun-Yoon and Jasper (1993) identified the problems with fit as the result of: (1) sizing systems being based on outdated anthropometric data and (2) sizing systems' lack of appropriate sizes to accommodate the full range of variation in body types that exist in the current population. Very few sizing systems accommodate differences in body proportions related to age, ethnicity or body weight (Winks, J, 1997;Goldsberry et al, 1996;Giddings & Boles, 1990). One of the problems encountered when designing for people, especially in South Africa with its multi-cultural population, is that they are different; for instance, tall or short, slim or fat, long arms, short legs, big heads, small feet, young or old (Ashby, 1978:1).…”
Section: Literature Backgroundmentioning
confidence: 99%